Implementasi Konsep Growth Mindset dalam Menumbuhkan Sikap Kewirausahaan pada Peserta Didik SMA - Suprayogi, Yogi; Pringgabayu, Dematria; Ramadhian, Mochamad Arief Rahman; Pawitra, Mohammad Tyas (Apik Cahaya Ilmu, 2025)
Developing an entrepreneurial mentality in high school students is crucial to equip the younger generation to face the challenges of entrepreneurship in a dynamic era. This community service program focuses on the application of a growth mindset as an important foundation in building a mindset that believes that intelligence and ability can be developed through effort, learning, and perseverance. Through interactive training, mentoring by business practitioners, case studies, and business idea competitions, students are encouraged to adopt a mindset that is open to failure as a learning opportunity and dares to try and innovate. With the transformation from a fixed mindset to a growth mindset, this program aims to improve an adaptive, innovative, and resilient entrepreneurial mentality. The expected result is an increase in students' readiness to face entrepreneurial opportunities and a positive contribution to the entrepreneurial ecosystem in the school and community environment